2017
DOI: 10.1080/01612840.2017.1373174
|View full text |Cite
|
Sign up to set email alerts
|

Relation Among Anxiety and Family Burden in Primary First-Degree Caregivers of Outpatients with Mental Disorders in Turkey

Abstract: The aim of this study was to determine the relation among anxiety and family burden in primary first-degree relative caregivers of outpatients with mental disorders in Turkey. Data were collected with patients' primary first-degree relative caregivers via the Information Form, Beck Anxiety Inventory (BAI), and Perceived Family Burden Scale (PFBS). In all, 481 caregivers (325 women and 156 men) participated in this study. Based on this study's results, primary caregivers of patients with mental disorders had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Our results enabled us to know the details of how work and care activities affect HWs and CHWs’ health, with the aim of designing psychosocial and educational interventions to prevent the risks derived from the activity they perform. Interventions should be directed through physical health programmes in order to improve their sleep quality [64], psychosocial programmes for caregivers that provide them with information regarding the disease and how to treat it at each stage, offering emotional support, and implementing strategies to cope, manage stress [65], and reduce anxiety [66] and sedentary behaviour [67], encouraging a healthy alternative to caregiving [68] that includes positive connotation variables, facilitating a change in the perception of their overload and overall health condition, with the objective of providing a higher level of satisfaction and better life qualify indices [69].…”
Section: Discussionmentioning
confidence: 99%
“…Our results enabled us to know the details of how work and care activities affect HWs and CHWs’ health, with the aim of designing psychosocial and educational interventions to prevent the risks derived from the activity they perform. Interventions should be directed through physical health programmes in order to improve their sleep quality [64], psychosocial programmes for caregivers that provide them with information regarding the disease and how to treat it at each stage, offering emotional support, and implementing strategies to cope, manage stress [65], and reduce anxiety [66] and sedentary behaviour [67], encouraging a healthy alternative to caregiving [68] that includes positive connotation variables, facilitating a change in the perception of their overload and overall health condition, with the objective of providing a higher level of satisfaction and better life qualify indices [69].…”
Section: Discussionmentioning
confidence: 99%
“…Dikec et al (31) found that all participating parents were stigmatized in many areas and tried to hide their child's diagnosis (31). Oz et al (37) conducted a study with mothers of children and adolescents who had Autism Spectrum Disorder (ASD) (N = 69) and examined the relationship between mothers' internalized stigmatization perception, depressive symptom level, anxiety symptoms, and quality of life. The level of internalized stigmatization was found to be moderate.…”
Section: Discussionmentioning
confidence: 99%
“…The level of internalized stigmatization was found to be moderate. It was also found that most of the mothers had low quality of life scores and also low life satisfaction scores (37). Özaslan and Yıldırım (55) conducted a study with mothers of children who had attention deficit hyperactivity disorder andfound that mothers experienced internalized stigmatization (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations